"A new biography of Jorge Luis Borges (1899-1984)" Milenko Paich as quasi biography (Literatures of the World: Poetics, Mentality and Spirituality, 2013)
The events of the work of Milenko Paich connected with the personality of Borges do not correspond to the specific of the genre of biographical narrative, there’s no scientific chronology of the protagonist’s life, and it can mean only one thing – it’s a quasi biography. The author takes in account a few facts of the writer’s life story and the rest of it he represents as a plot of his immagination, in particular, conversations, inner worries, process of creating his works, creating an image that has very few common features with real Borges.
Keywords: biography; quasi biography; mystification